Effects of Low Laser Therapy in Fixed Orthodontic Treatment: Systematic Review - Kumar, Kishore; Hussein, Adam; Qamruddin, Irfan; Khatri, Tamana; Alam, Mohammad Khursheed (Pakistan Armed Forces Medical Journal, 2025)
Objective: to determine how low-level laser therapy affects patients' early pain thresholds and the level of tooth movement brought on by orthodontic treatments.Study Design: Systematic review.Methodology: Various electronic databases (Google Scholar 145, PubMed = 534, NCBI = 18, and Cochrane = 42) were searched for 743 papers for this purpose. Ten publications were chosen for the systematic review of our topic of interest.Results: Seven of the ten studies examined for evidence had strong evidence, while just three included moderate evidence. Four of the seven studies with strong evidence had statistically significant conclusions. Three studies with intermediate evidence have shown significant results. LLLT may thereby promote orthodontic tooth movement, according to the evidence. Conclusion: According to a thorough evaluation of the scientific literature, there is no evidence that LLLT by diode laser increases immediate orthodontic discomfort, although it does encourage orthodontic tooth movement. Limited laser treatment is also helpful for treating discomfort and relieving pain.